Non-financial Rewards and Employee Engagement: A Case Study of Uganda’s Health Sector - Xavier Okwii (Uganda Christian University, 2023)
This research explores the concept of non-financial rewards and employee engagement among employees in Uganda’s health sector.it sets to identify the various types of non-financial rewards such as employee recognition programs, flexible work hours, opportunities for training and professional development, career development, and job security among others that influence the level of employee engagement. The study was also carried out to evaluate the effects of non-financial rewards on employee engagement and as well assess the relationship between non-financial rewards and employee engagement. The study was conducted on a population sample size of 80 respondents at Mukono General Hospital. Respondents comprised of doctors, nurses, hospital administrators, medical technicians, midwives and other staff. Data was collected using a 5 point likert scale. First the overall responses were analyzed and then the group responses were also analyzed using regression analysis. The results revealed that the biggest percentage of the respondents showed positive response towards non-financial rewards as being offered and there were differences in responses towards each subset of non-financial rewards. Further studies also indicated a high percentage of the respondent’s response on employee engagement due to the provision of non-financial rewards and how these non-financial rewards generally affect their level of engagement with Mukono General Hospital.
This is a dissertation.